Are YouTube videos useful for patient self-education in type 2 diabetes?. (March 2020) - Gimenez-Perez, Gabriel; Robert-Vila, Neus; Tomé-Guerreiro, Marta; Castells, Ignasi; Mauricio, Didac
Objective: To evaluate the usefulness of YouTube videos as an educative tool for type 2 diabetes self-management. Design: Search terms were "diabetes diet" and "diabetes treatment." Videos were jointly assessed by two reviewers. A third investigator evaluated a random sample to check for agreement. Main measures: Usefulness defined as making reference to AAD7 Self-Care Behaviors ™ and presence of misleading information. Results: Of the 393 videos included, 42.2 percent (n = 166) classified as "alternative medicine." 40.2 percent (n = 158) contained useful information. 25.7 percent (n = 101) videos contained misleading information. Videos displaying "alternative medicine" professionals (60 out of 200) were less useful (17% vs 57%; p < 0.001) and more misleading (40% vs 2%; p < 0.001). Conclusion: The probability of finding videos that relate to AADE7 ™ self-care behaviors is below 50 percent. The odds of finding misleading information are high. Therefore, it is inadvisable for professionals to recommend the use of YouTube as an educating tool if specific videos are not suggested.